Recyclable Polystyrene-Supported Copper Catalysts for the Aerobic Oxidative Homocoupling of Terminal Alkynes - Yan, Shuo; Pan, Shiguang; Osako, Takao; Uozumi, Yasuhiro (Synlett, 2016)
Polystyrene-supported copper(II) N,N,N′,N′-tetraethyldiethylenetriamine [Cu(II)–TEDETA] complexes were prepared by immobilization of TEDETA onto crosslinked polystyrene resin, followed by complexation with copper salts. The polystyrene-immobilized CuSO4–TEDETA complex efficiently catalyzed the oxidative homocoupling of terminal alkynes under air to give the corresponding 1,3-diynes in up to 99% yield. The catalyst was easily recovered by simple filtration and reused eight times without significant loss of catalytic activity.
Keywords: termial alkynes; 1,3-diynes; homocoupling; polystyrene; copper sulfate